2014
DOI: 10.1186/1755-1536-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast administration reduces fibrosis and improves fatigue resistance in muscles of mdx dystrophic mice

Abstract: BackgroundDuchenne muscular dystrophy (DMD) is a severe and progressive muscle-wasting disorder caused by mutations in the dystrophin gene that result in the absence of the membrane-stabilising protein dystrophin. Dystrophic muscle fibres are susceptible to injury and degeneration, and impaired muscle regeneration is associated with fibrotic deposition that limits the efficacy of potential pharmacological, cell- and gene-based therapies. Novel treatments that can prevent or attenuate fibrosis have important cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
3
30
0
1
Order By: Relevance
“…The concentration and quality of RNA samples were determined using Nanodrop 2000 spectrophotometer (Thermo Scientific, Waltham, MA, USA). Real-time RT-PCR was performed as described previously [30] using the following forward and reverse primer sequences: SOCS3, 5′-GCTGGCCAAAGAAATAACCA-3′ and 5′- AGCTCACCAGCCTCATCTGT-3′. Relative gene expression was calculated using the expression 2 −ΔCT , normalized to total complementary DNA (cDNA) content as determined using Qubit 2.0 Fluorometer (Life Technologies, Carlsbad, CA, USA), as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration and quality of RNA samples were determined using Nanodrop 2000 spectrophotometer (Thermo Scientific, Waltham, MA, USA). Real-time RT-PCR was performed as described previously [30] using the following forward and reverse primer sequences: SOCS3, 5′-GCTGGCCAAAGAAATAACCA-3′ and 5′- AGCTCACCAGCCTCATCTGT-3′. Relative gene expression was calculated using the expression 2 −ΔCT , normalized to total complementary DNA (cDNA) content as determined using Qubit 2.0 Fluorometer (Life Technologies, Carlsbad, CA, USA), as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
“…The concentration and quality of RNA samples was determined using Nanodrop 2000 spectrophotometer (Thermo Scientific, Waltham, MA, USA). Real-time RT-PCR was performed as described previously [30] using the following forward and reverse primer sequences: MCK, 5′-CACCATGCCGTTCGGCAACA-3′ and 5′-GGTTGTCCACCCCAGTCT-3′; SOCS3, 5′-GCTGGCCAAAGAAATAACCA-3′ and 5′-AGCTCACCAGCCTCATCTGT-3′; Pax7, 5′-GGAAAACCAGTGTGCCATCT-3′ and 5′-CCTTGTCTTTGGCACCATTT-3′; MyoD, 5′-AGTGAATGAGGCCTTCGAGA-3′ and 5′-GCATCTGAGTCGCCACTGTA-3′; Myogenin, 5′-CACTCCCTTACGTCCATCGT-3′ and 5′-CAGGACAGCCCCACTTAAAA-3′; IL-6, 5′-CCGGAGAGGAGACTTCACAG-3′ and 5′-TCCACGATTTCCCAGAGAAC-3′; TNF-α, 5′-GGCCTTCCTACCTTCAGACC-3′ and 5′-AGCAAAAGAGGAGGCAACAA-3′; IFN-γ, 5′-ACTGGCAAAAGGATGGTGAC-3′ and 5′-TGAGCTCATTGAATGCTTGG-3′; F4/80, 5′-CATCAGCCATGTGGGTACAG-3′ and 5′-CATCACTGCCTCCACTAGCA-3′; CD68, 5′-TCCAAGCCCAAATTCAAATC-3′ and 5′-ATTGTATTCCACCGCCATGT-3′. Gene expression was quantified using a cycle threshold (C T ) method.…”
Section: Methodsmentioning
confidence: 99%
“…The mdx mouse is a very useful model but fails to reproduce key symptoms of DMD patients such as muscular weakness 2 . Thus, although several immunotherapies were successful in mdx mice, such as intravenous immunoglobulin 18 , anti-TNFα antibodies 19 , IL-6 blocking 20 , tranilast 21 , heme oxygenase-1 (HO-1) inducers 22 , IL-1 receptor antagonist 23 and IL-2 complexes to amplify CD4 + Tregs 12 , their potential effect in DMD patients is uncertain. Dmd mdx rats reproduce skeletal and cardiac muscular weakness at early time points and develop skeletal and cardiac muscle tissue lesions that resemble those observed in DMD patients 3, 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that dominant-negative inhibition of endogenous TRPV2 in mdx mice suppressed the calcium increase in muscle fibers and eased dystrophic pathology, that is, the increased number of central nucleus and fiber size variability/fibrosis/apoptosis, elevated serum creatine kinase levels, and reduced muscle performance 33. Tranilast, a clinically used antiallergic drug, is also known to be a TRPV2 blocker experimentally,34 and its administration was found to be efficacious in reducing serum creatine kinase levels in mdx mice35 and fibrosis in mdx skeletal muscles, leading to improved resistance to muscle fatigue 36…”
Section: Potential Drugs Targeting Inflammatory Mechanisms In Dmdmentioning
confidence: 99%